Między piekłem a niebem – językowy obraz wiary w górnołużyckich przysłowiach. - Bura, Renata (Slavia Occidentalis, 2014)
Proverbs express the opinions of the populace on life and the surrounding world. The question of faith occupies an important place among the commented topics. The picture of faith of Lusatians – as seen through the prism of the vision of heaven and hell preserved in the Upper Lusatian proverbs – seems to be quite interesting. On the one hand, it confirms stereotypical conceptions of heaven and hell as a space between two opposite poles which are good and evil. Heaven is the supreme value and the place of reward for suffering on earth, whereas hell is the place of punishment for the committed sins, the place from which there is no return. Moreover, the proverbs show distinctly that moral principles are clearly determined and closely linked with the teachings of the Church. On the other hand, they allow one to become acquainted with social relationships prevailing in the Lusatian countryside in the bygone centuries.